2007
DOI: 10.1038/sj.npp.1301521
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Depletion of the Prefrontal Cortex Induces Dendritic Spine Loss: Reversal by Atypical Antipsychotic Drug Treatment

Abstract: Dystrophic changes in dendrites of cortical neurons are present in several neuro-psychiatric disorders, including schizophrenia. The mechanisms that account for dendritic changes in the prefrontal cortex (PFC) in schizophrenia are unclear. Cognitive deficits in schizophrenia have been linked to compromised cortical dopamine function, and the density of the PFC dopamine innervation is decreased in schizophrenia. We determined if 6-hydroxydopamine lesions of the ventral tegmental area that disrupt the PFC dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 95 publications
8
63
1
Order By: Relevance
“…The cognitive deficits resulting from a lesion-induced dopaminergic dysfunction in PFC is known to be severe (Brozoski et al, 1979), supporting the potential link between DA neurotransmission and cognitive function. The morphological consequences of a disruption to DA transmission in PFC has been demonstrated by a recent study, which showed that selective damage to the dopaminergic innervation of PFC causes a loss of dendritic spines on pyramidal cells in the rat, whereas the restoration of dopaminergic tone with olanzapine reversed this effect (Wang and Deutch, 2008). Our data builds on the data of Wang and Deutch (2008) by demonstrating that that olanzapine treatment counteracts the asymmetric synapse loss in the PFC induced in the PCP model.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The cognitive deficits resulting from a lesion-induced dopaminergic dysfunction in PFC is known to be severe (Brozoski et al, 1979), supporting the potential link between DA neurotransmission and cognitive function. The morphological consequences of a disruption to DA transmission in PFC has been demonstrated by a recent study, which showed that selective damage to the dopaminergic innervation of PFC causes a loss of dendritic spines on pyramidal cells in the rat, whereas the restoration of dopaminergic tone with olanzapine reversed this effect (Wang and Deutch, 2008). Our data builds on the data of Wang and Deutch (2008) by demonstrating that that olanzapine treatment counteracts the asymmetric synapse loss in the PFC induced in the PCP model.…”
Section: Discussionsupporting
confidence: 67%
“…The morphological consequences of a disruption to DA transmission in PFC has been demonstrated by a recent study, which showed that selective damage to the dopaminergic innervation of PFC causes a loss of dendritic spines on pyramidal cells in the rat, whereas the restoration of dopaminergic tone with olanzapine reversed this effect (Wang and Deutch, 2008). Our data builds on the data of Wang and Deutch (2008) by demonstrating that that olanzapine treatment counteracts the asymmetric synapse loss in the PFC induced in the PCP model. Furthermore, the ability of olanzapine to restore asymmetric synapse number when given acutely is consistent with a dopaminergic mechanism, as a rapid elevation of DA levels in the PFC is induced by olanzapine, which lasts at least 120 min after i.p.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Chronic PCP treatment decreases parvalbumin mRNA expression and chronic administration of clozapine, but not haloperidol, reversed the PCP-induced decreases in parvalbumin mRNA expression in prefrontal cortical GABAergic interneurons (Cochran et al, 2003). Chronic treatment with olanzapine, but not haloperidol, has been reported to slow volume loss in the prefrontal cortex in a prefrontal cortical dopamine denervation model of schizophrenia (Wang and Deutch, 2008). Some clinical reports also suggest some atypical APDs may have a neuroprotective effect.…”
Section: Discussionmentioning
confidence: 98%